2021
DOI: 10.3390/foods10071523
|View full text |Cite
|
Sign up to set email alerts
|

How Do Consumers’ Food Values across Countries Lead to Changes in the Strategy of Food Supply-Chain Management?

Abstract: Although one of the main goals of supply-chain management is to maximize consumer values, the research to date has mainly focused on the supply side. In the case of the food industry, understanding consumer needs and maximizing its utility are essential. In this study, we analyze consumers’ 12 meta-values (e.g., safety, taste, health, price, environment, etc.), then suggest the strategy of food cold-chain management satisfying consumers’ perception. We focused on consumers from three countries in Asia: Korea, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Supporting the working environment ranks higher in Japan than in the other four countries. However, previous food value studies have revealed that Japanese consumers rank fairness, which partly includes a value corresponding to the activity for workers in this Same superscripts in each row indicate insignificant differences in BW ratio score distribution study, relatively lower (Jo and Lee 2021;Abe et al 2021). Although the definition of fairness in previous food value studies is broader than that of the activity for workers in this study, a significant factor causing the discrepancy may be a high awareness among the Japanese regarding the working environment because of the COVID-19 pandemic and corresponding limitations on daily activities (e.g., staying at home), which has social impacts (e.g., decrease in income and increase in unemployment).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Supporting the working environment ranks higher in Japan than in the other four countries. However, previous food value studies have revealed that Japanese consumers rank fairness, which partly includes a value corresponding to the activity for workers in this Same superscripts in each row indicate insignificant differences in BW ratio score distribution study, relatively lower (Jo and Lee 2021;Abe et al 2021). Although the definition of fairness in previous food value studies is broader than that of the activity for workers in this study, a significant factor causing the discrepancy may be a high awareness among the Japanese regarding the working environment because of the COVID-19 pandemic and corresponding limitations on daily activities (e.g., staying at home), which has social impacts (e.g., decrease in income and increase in unemployment).…”
Section: Discussionmentioning
confidence: 85%
“…In previous studies on food valuation, the said activity corresponds to safety, taste, and nutrition. Food value studies in the USA and Norway (Bazzani et al 2018) and in Japan (Jo and Lee 2021;Abe et al 2021) have revealed that safety was the first to third most important value, while taste and nutrition were the second to fifth most important values. Compared with these studies, the activity to ensure the quality and safety of milk ranks relatively lower in France, the Netherlands, and Italy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rong et al [ 25 ] showed that as China’s income and education levels increase, consumers will become more accepting of paying the cost of cold chain logistics and will pay relatively higher premiums. Jo et al [ 26 ] analyzed 12 meta-values of consumers and proposed a food cold chain management strategy to meet consumer perceptions.…”
Section: Introductionmentioning
confidence: 99%